Pulp and paper mill sludges decrease soil erodibility. Issue 1 (8th December 2020) - Rasa, Kimmo; Pennanen, Taina; Peltoniemi, Krista; Velmala, Sannakajsa; Fritze, Hannu; Kaseva, Janne; Joona, Juuso; Uusitalo, Risto
Abstract: Declining carbon (C) content in agricultural soils threatens soil fertility and makes soil prone to erosion, which could be rectified with organic soil amendments. In a 4‐yr field trial, we made a single application of three different organic sludges from the pulp and paper industry and studied their effects on cereal yield, soil C content, and fungal and bacterial composition. In laboratory rainfall simulations, we also studied the effects of the soil amendments on susceptibility to erosion and nutrient mobilization of a clay‐textured soil by measuring the quality of percolation water passing through 40‐cm intact soil monoliths during 2‐d rainfall simulations over four consecutive years after application. A nutrient‐poor fiber sludge reduced wheat yield in the first growing season, but there were no other significant effects on cereal yield or grain quality. An input of ∼8 Mg ha −1 C with the soil amendments had only minor effects on soil C content after 4 yr, likely because of fast microbe‐mediated turnover. The amendments clearly changed the fungal and bacterial community composition. All amendments significantly reduced suspended solids (SS) and total phosphorus (TP) concentrations in percolation water. The effect declined with time, but the reduction in SS and TP was still >25% 4 yr after application. We attributed the lower tendency for particle detachment in rain simulations to direct interactions of soil minerals with the added particulate organic matter and microbe‐derived compounds that stabilize soil aggregates. In soils with low organic matter content, pulp and paper industry by‐products can be a viable measure for erosion mitigation. Core Ideas: Erosion mitigation using pulp and paper mill sludges was tested in a 4‐yr study. Intact soil monoliths were taken from field for laboratory rainfall simulations. Sludge addition reduced particle and P losses from soil to percolation water. Sludges decomposed quickly and had minor effects on soil C content after 4 yr. Sludge addition clearly altered soil bacterial and fungal community composition.